Accessibilities in public recreational park for people with disabilities / Norfaezah Mohd Rosli - Mohd Rosli, Norfaezah (2017)
Accessibility of public recreation parks is important to people with disabilities, as it may influence their physical activity participation, health benefit and quality of life. The purpose of this study was to identify the physical factors that are pertinent to the accessibility of public recreational park to people with disabilities in Malaysia. An assessment instrument named Accessibility at Recreational Park Instrument (ARPI) was developed with reference to subscales in Accessibility Instruments Measuring Fitness and Recreation Environments (AFMFREE) by Rimmer, Riley, Wang and Rauworth (2004). The accessibility questions were developed with reference to Code of Practice for Access of Disabled person to Public and Outside Building; Malaysian Standard MS 1184:2002 and Malaysian Standard MS 1331:2003 as to suits with Person with Disabilities Act 2008 in Malaysia. Confirmatory Factor Analysis (CFA) was performed to confirm the reliability (r=0.85) and validity of the instrument. The Five dimensions identified were Access Routes, Ease of Access, Signage, Toilet, and Lighting. This study was conducted at Titiwangsa Lake Park, Kuala Lumpur, involving people with different disabilities, which include wheelchair users (n = 107), amputees (n = 53) and assistive aids user (n = 11). The volunteer respondents were visitors to the public recreation park, aged above 18 years old. The results showed that, 'Toilet' was found to be the most important factor for two groups (wheelchair users and amputees).In the Titiwangsa Lake Park, respondents perceived 'Access Routes' as the most accessible compared to other accessibility factors. There were no significant differences in the five accessibility factors for all types of disabilities. However, there were significance differences of importance in terms of "Signage" between difference age groups; that is between 18- 24 years old and 45-55 years old group. Hence, public recreational park providers need to consider more seriously the above accessibility factors as to promote active participation of people with disabilities. Subsequently, this active involvement in recreation activities could improve their quality of life.